APLIKASI PROGRAMMABLE LOGIC CONTROLLER (PLC) OMRON CP1E NA20 DRA DALAM PROSES PENGATURAN SISTEM KERJA MESIN PEMBUAT PELET IKAN - Dewi, Tiar Kusuma; Sasmoko, Priyo (Vocational School Diponegoro University, 2014)
Tiar Kusuma Dewi, Priyo Sasmoko, in paper application of programmable logic controller (PLC) omron CP1E NA20 DRA in control system of fish pellets builders engine explain that better known as PLC or Programmable Logic Controller is an electronic apparatus that works digitally , has a programmable memory , save the commands to perform specific functions such as logic , timing , counting and arithmatik to control different types of machines or processes through modules input / output analog or digital . PLC will run the display module according to the mnemonic code is entered into the PLC via the Programming Console or the CX - Programmer programs . However , here are discussed PLC using the CX - Programmer . OMRON PLC used is CP1E NA20 DRA . PLC works by observing input ( via sensors related ) , then the process and take action as needed , ie turn on or turn off the output ( logic 0 or 1 ) . Users create a program that will then be executed by the PLC in question , so that the tool Fish Pellet Machine Manufacturers Automatic will work as desired . Keyword : OMRON PLC CP1E NA30 DRA , the CX - Programer